ANALISIS DIMENSI WATAK TOKOH DALAM FILM YANG TAK TERGANTIKAN KARYA HERWIN NOVIANTO - Keassy Ramayanti Simanjuntak; Suhardi; Maulida Mustado; Legi Elfitra; Ahada Wahyusari; Dody Irawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the psychological, physiological, and sociological dimensions of the characters in the film Yang Tak Tergantikan by Herwin Novianto using an objective approach. This study uses a qualitative descriptive method. The data collection techniques used are watching, listening, and taking notes. The data analysis technique used is the content analysis technique. The results of this study obtained various character traits using psychological, physiological, and sociological dimensions. The psychological dimension aspects are: kind, patient, generous, forgiving, brave, and angry. The physiological aspects are: age, physical characteristics, and personal condition. The sociological aspects are: ethnicity, gender, rank/position, profession/occupation.